The Venetian Instrumental Concerto During Vivaldi's Time - Wilk, Piotr (Eastern European Studies in Musicology, 2020)
It is the first monograph in which the concertos of all composers active in this field in the Republic of Venice in the years 1695-1740 are methodically discussed. The Venetian instrumental concerto from Vivaldi's time is portrayed here through an extensive and thorough survey of the most complete and representative musical material that allowed for the making of conclusions as to its typology, form, style and technique. The concertos discussed here include 974 works by fifteen composers active in Venice, Brescia, Bergamo and Padua. Such an approach not only gives an exhaustive but also a more objective view on the history of the Baroque concerto in its Venetian variant. It shows Vivaldi's work in a new and broad context, which allows us to better understand its unique character.